A pH-sensitive nanocarrier for co-delivery of doxorubicin and camptothecin to enhance chemotherapeutic efficacy and overcome multidrug resistance in vitro. Issue 94 (14th October 2015) - Li, Zhen; Li, Hongmei; Liu, Lixiang; You, Xinyi; Zhang, Chaofeng; Wang, Yue
<x xml:space="preserve">Abstract</x> A pH-sensitive drug delivery system of HSNPs sealed with ZnO QDs nanocarrier, where the HSNPs have the large hollow interiors for delivering hydrophobic camptothecin and the mesoporous structure for delivering hydrophilic doxorubicin.